Cost-Minimization Analysis of Dexmedetomidine Compared to Other Sedatives for Short-Term Sedation During Mechanical Ventilation in the United States - Aggarwal J; Lustrino J; Stephens J; Morgenstern D; Tang WY (Dove Medical Press, 2020)
Jyoti Aggarwal,1 Jacqueline Lustrino,1 Jennifer Stephens,2 Diana Morgenstern,3 Wing Yu Tang4 1Pharmerit International, Newton, MA, USA; 2Pharmerit International, Bethesda, MD, USA; 3Pfizer, Collegeville, PA, USA; 4Pfizer, New York, NY, USACorrespondence: Wing Yu TangPfizer, 235 E. 42nd St, New York, NY 10017, USAEmail wingyu.tang@pfizer.comPurpose: Mechanical ventilation (MV) remains a substantial cost driver in intensive care units (ICU) in the United States (US). Evaluations of standard sedation treatments used to relieve pain and discomfort in this setting have found varying impacts on ICU length of stay. This cost analysis examines both length-of=stay costs and the total cost implications among MV patients receiving common sedative treatments (dexmedetomidine, propofol, or midazolam) in short-term sedation settings (< 24 hours).Methods: A cost-minimization model was conducted from the hospital provider perspective. Clinical outcomes were obtained from published literature and included ICU length of stay, MV duration, prescription of sedatives and pain medication, and the occurrence of adverse events. Outcomes costs were obtained from previously conducted ICU cost studies and Medicare payment fee schedules. All costs were estimated in 2018 US Dollars.Results: The per patient costs associated with dexmedetomidine, propofol, and midazolam were estimated to be $21,115, $27,073, and $27,603, respectively. Dexmedetomidine was associated with a savings of $5958 per patient compared to propofol and a saving of $6487 compared to midazolam. These savings were primarily driven by a reduction in ICU length of stay and the degree of monitoring and management.Conclusion: Dexmedetomidine was associated with reduced costs when compared to propofol or midazolam used for short-term sedation during MV in the ICU, suggesting sedative choice can have a potential impact on overall cost per episode.Keywords: sedation, dexmedetomidine, midazolam, propofol, costs, model